More Than a Quarter of a Century: The Doctoral Programme at Oslo School of Architecture and Design: notes on the development of education since 1981 - Dunin-Woyseth, Halina (FormAkademisk, 2008)
This paper is intended to present how the Doctoral Programme at the Oslo School of Architecture and Design (AHO, also referred to as the school later in this paper) has developed since 1981.   The paper focuses on the organised research education which has been offered at the school since 1992. Although the school has been the main engine of these doctoral studies, (mainly because it has had the right to confer the doctoral degrees), it has cooperated with other kindred institutions in a mutual learning process. The paper examines in turn the eight volumes of the Research Magazine, which discusses the development of the Doctoral Programme at the school. The paper concludes with a brief evaluation regarding the doctoral programme at the AHO. In the postscript closing the paper, some contributors who have made this development possible are mentioned.